Engineering Societies in the Agents World VII 7th International Workshop, ESAW 2006 Dublin, Ireland, September 6-8, 2006 Revised Selected and Invited Papers - O'Hare, Gregory; Ricci, Alessandro; O'Grady, Michael; Dikenelli, Oguz (Lecture Notes in Artificial Intelligence, 2007)
The seventh international workshop ESAW 2006 - Engineering Societies in the Agents World VII-was hosted in the School of Computer Science and Inf- matics, University College Dublin, Ireland in September 2006. This workshop was organized as a stand-alone event, running over three days, and continued andenhancedthe high-qualityconferencetheme thatnowuniquelycharacterizes the ESAW workshop series. ESAW VII built upon the success of prior ESAW workshops - Ku¸ sadasi (2005), London (2004) and Toulouse (2004), going back to the inauguralworkshopheld in Berlin(2000). This workshopwasattended by 50 participants from 13 di?erent countries. Over 25 researchers presented their work and substantial time was allocated each day for ad-hoc interactive disc- sions on those presented topics. Indeed, these opportunities for the exchange of views and open discussion with fellow experts are one of the hallmarks of the ESAW series. Discussions coalesced around ESAW's main themes: - Engineering multi-agent systems - Methodologies for analysis, design, development and veri?cation of agent societies - Interaction and coordination in agent societies - Autonomic agent societies - Trust in agent societies For moreinformationabouttheworkshop,theinterestedreaderisreferredto 1 the ESAW 2006 WWW site . The original contributions have been published as a Technical Report (UCD-CSI-2006-5) and this may be obtained freely from the Technical Report section on the WWW page of the School of Computer Science 2 and Informatics at University College Dublin . These post-proceedings continue the series published by Springer (ESAW 2000: LNAI 1972; ESAW 2001: LNAI 2203; ESAW 2002: LNAI 2577; ESAW 2003: LNAI 3071; ESAW 2004: LNAI 3451; ESAW 2005: LNAI 3963).